Plutonium Bioassay Testing of United States Atmospheric Nuclear Test Participants and Occupation Forces of Hiroshima and Nagasaki, Japan. Issue 4 (October 2017) - Schaeffer, Dennis Michael; Case, David R.; Ingraham, Joanna T.; Blake, Paul K.
Abstract : Abstract: The pilot urine plutonium bioassay testing program engaged 100 atomic veterans and 58 persons representative of the United States general population using the fission track analysis technique, developed by Brookhaven National Laboratory. The methodology, collected data, scientific challenges, and test results are presented herein. The Defense Threat Reduction Agency and its predecessor agencies conducted this program in the late 1990s to the mid‐2000s to determine the feasibility of bioassay testing to supplement dose reconstruction to estimate atomic veterans' doses under the agency's Nuclear Test Personnel Review Program. In summary, 239 Pu urine bioassay using fission track analysis showed inconsistencies in sample measurement repeatability. To use the analysis as a tool to enhance current processes to perform accurate dose reconstructions requires extensive understanding and resolution of the measurement inconsistencies well beyond the scope of this pilot study. Therefore, fission track analysis (FTA) was found not feasible for implementation on a wide scale basis for atomic veterans.